2018
DOI: 10.1093/jxb/ery303
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation of wheat grains contributes to a stable filling rate under heat stress

Abstract: When wheat is subjected to heat stress during grain filling, metabolic adaptation reallocates resources to deposition of reserves and prioritizes a stable filling rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…The growth, yield and quality of wheat are adversely affected by global climate changes, particularly increasing temperatures (heat stress, HS) (Tingley and Huybers, ; Lobell and Tebaldi, ; Tack et al ., ; Lesk et al ., ). Each degree Celsius increase in global mean temperature would reduce wheat yield by 6.0% (Zhao et al ., ), and this reduction is most severe during the grain‐filling stage (Wollenweber et al ., ; Farooq et al ., ; Tack et al ., ; Lesk et al ., ; Wang et al ., 2018a). A comprehensive understanding of the heat responses and adaptations, especially at the grain‐filling stage, is therefore urgently required to enable the development of practices to improve wheat thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth, yield and quality of wheat are adversely affected by global climate changes, particularly increasing temperatures (heat stress, HS) (Tingley and Huybers, ; Lobell and Tebaldi, ; Tack et al ., ; Lesk et al ., ). Each degree Celsius increase in global mean temperature would reduce wheat yield by 6.0% (Zhao et al ., ), and this reduction is most severe during the grain‐filling stage (Wollenweber et al ., ; Farooq et al ., ; Tack et al ., ; Lesk et al ., ; Wang et al ., 2018a). A comprehensive understanding of the heat responses and adaptations, especially at the grain‐filling stage, is therefore urgently required to enable the development of practices to improve wheat thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the heat signal is probably transduced by several pathways to converge on heat shock factors (HSFs), followed by activation of a number of heat shock proteins (HSPs) and other heat‐responsive genes that drive the heat adaptation process in plants (Kotak et al ., ; Saidi et al ., ; Bokszczanin et al ., ). This heat adaptation confers thermotolerance on plant growth and development, and majorly contributes to maintaining the grain‐filling rate and the final yield of crops under HS (Wang et al ., 2018a). However, how plants sense HS and which pathways are involved in heat sensing and signaling to activate heat adaptation are largely unknown, hindering our full understanding of plant thermotolerance.…”
Section: Introductionmentioning
confidence: 99%
“…In wheat grains, comparative proteomic analysis has shown that water deficit and heat stress usually leads to decreases in protein synthesis/assembly components and metabolism-related proteins, but the stress/defense-related proteins and seed storage proteins are often increased, especially under heat stress [ 53 , 54 ]. Indeed, WS, HS, and WH treatments all led to significant increases in grain protein content (GPC) in DBA Aurora.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, heat stress affects the biosynthesis of secondary metabolites and biosynthesis of aminoacyl-tRNA [25]. The metabolic profiling of what grains using LC-MS/MS-HPLC technologies indicated higher concentrations of sucrose and G1p under heat stress [156]. Comparative metabolomics analysis was carried out for heat-tolerant and -susceptible soybean cultivars.…”
Section: Temperature Stress Regulationmentioning
confidence: 99%